CD36 is important for adipocyte recruitment and affects lipolysis. (29th May 2013) - Vroegrijk, Irene O.C.M.; van, Jan Bert; van, Janna A.; van, Sjoerd A.A.; Febbraio, Maria; Steinbusch, Laura K.M.; Glatz, Jan F.C.; Havekes, Louis M.; Voshol, Peter J.; Rensen, Patrick C.N.; van, Ko Willems; van, Vanessa
<x xml:space="preserve">Abstract</x> Objective: The scavenger receptor CD36 facilitates the cellular uptake of long‐chain fatty acids. As CD36‐deficiency attenuates the development of high fat diet (HFD)‐induced obesity, the role of CD36‐deficiency in preadipocyte recruitment and adipocyte function was set out to characterize. Design and Methods: Fat cell size and number were determined in gonadal, visceral, and subcutaneous adipose tissue of CD36−/− and WT mice after 6 weeks on HFD. Basal lipolysis and insulin‐inhibited lipolysis were investigated in gonadal adipose tissue. Results: CD36−/− mice showed a reduction in adipocyte size in all fat pads. Gonadal adipose tissue also showed a lower total number of adipocytes because of a lower number of very small adipocytes (diameter <50 μm). This was accompanied by an increased pool of preadipocytes, which suggests that CD36‐deficiency reduces the capacity of preadipocytes to become adipocytes. Regarding lipolysis, in adipose tissue from CD36−/− mice, cAMP levels were increased and both basal and 8‐bromo‐cAMP stimulated lipolysis were higher. However, insulin‐mediated inhibition of lipolysis was more potent in CD36−/− mice. Conclusions: These results indicate that during fat depot expansion, CD36‐deficiency negatively affects preadipocyte recruitment and that in mature adipocytes, CD36‐deficiency is associated with increased basal lipolysis and insulin responsiveness.